The importance of student monitoring in academic learning: A two-year follow-up - Nunes, Gabriel Pereira [UNESP]; Pirovani, Beatriz Ommati [UNESP]; Silva, Hiago Guimarães; Butarelo, Ana Victória [UNESP]; Rossini, Juliana da Silva [UNESP]; Costa, Jefferson Martins [UNESP]; Nunes, Larissa Pereira; Martins, Karina Vieira [UNESP] (Universidade Estadual de Campinas, 2018)
Monitory exercises must provide conditions that support academic and personal development for students during graduation, once it allows a leveling possibility whereas the monitor meets the demands from the students in earlier years. Aim: This study has as objective to analyze the importance of monitory in advantage of the best academic achievement in students. Methods: In the years of 2015 and 2016, sophomore odontology students were monitored on pharmacology, originated from the need of remedial studies due to its high incidence of failure. For such, weekly monitoring on theoretical classes, study groups and content reviews were done. After two years of monitoring the number of failures and respective percentages were determined. The data was submitted to variance analysis and Student-Newman-Keuls test (p < 0,001). Results: The monitory had expressive results, since it reduced significantly failure numbers, statistically much inferior than previous years. Conclusion: Hence, it was possible to verify that monitory had positive effects on students learning, allowing access to knowledge and being imperative to the covered content systematization on the subject, since advising and monitoring students made their learning more natural.
Keywords: Learning; Pharmacology; Student monitoring